THEORETICAL ASPECTS OF THE FORMATION OF PERSONNEL SECURITY IN AN INDUSTRIAL ENTERPRISE (Development Service Industry Management, 2024)
Ensuring the safety of employees and maintaining the stability of business processes becomes a critically important task for enterprises in the conditions of martial law in Ukraine. The implementation of personnel security is carried out at the expense of defining goals and measures that contribute to ensuring the personnel security of the enterprise. The main goals of the company's personnel security include: protection against personnel risks, ensuring the stability of personnel, improving the qualifications and development of employees, ensuring effective communication and interaction, developing employee loyalty and corporate culture, ensuring social and legal protection of employees. Defining clear and achievable goals in the field of personnel security allows you to minimize the risks associated with the human factor and ensure the stable and safe operation of the enterprise. The goals of the company's personnel security should be comprehensive and aimed at creating conditions that ensure protection, stability and development of personnel potential. The article provides a list of measures for each of the identified goals that ensure their implementation. In order to effectively manage the company's personnel security, it is necessary to establish clear goals that will correspond to the specific components of this security. The article examines the components of personnel security of the enterprise and singles out those that make up more than 30%, they include: anti-conflict security, life security, health security, intellectual security, information security, career security, pension and insurance security, professional security , psychological safety, social-motivational safety, technological safety, physical safety, financial safety. Each of these components requires clear goals and measures to achieve them. This approach allows the enterprise to systematically manage personnel risks, increase the motivation and satisfaction of employees, and ensure stability and efficiency of work.
Keywords: security; personnel security; personnel risks; components of personnel security; management